Antibody responses in blood and saliva post COVID-19 bivalent booster do not reveal an Omicron BA.4/BA.5- specific response - Baker, Ryan; Lawlor, Rebecca; Smith, Maeve; Price, Jessica; Eaton, Ashley; Lover, Andrew; Alfandari, Dominique; Reinhart, Peter; Arcaro, Kathleen F.; Osborne, Barbara A. (Frontiers in Immunology, 2024)
Introduction Current SARS-CoV-2 strains continue to mutate and attempt to evade the antibody response elicited by previous exposures and vaccinations. In September of 2022, the first updated SARS-CoV-2 vaccines, designed to create immune responses specific for the variants circulating in 2022, were approved. These new vaccines, known commonly as the bivalent boost(er), include mRNA that encodes both the original Wuhan-Hu-1 spike protein as well as the spike protein specific to the Omicron BA.4 and BA.5 variants. Methods We recruited volunteers from University of Massachusetts student, faculty and staff members to provide samples of blood and saliva at four different time points, including pre-boost and three times post boost and analyzed samples for antibody production as well as neutralization of virus. Results Our data provide a comprehensive analysis of the antibody response following a single dose of the bivalent boost over a 6-month period and support previous findings that the response induced after the bivalent boost does not create a strong BA.4/BA.5-specific antibody response. Conclusion We found no evidence of a specific anti-BA.4/BA.5 response developing over time, including in a sub-population of individuals who become infected after a single dose of the bivalent booster. Additionally, we present data that support the use of saliva samples as a reliable alternative to blood for antibody detection against specific SARS-CoV-2 antigens.